2017
DOI: 10.17161/jas.v3i2.6492
|View full text |Cite
|
Sign up to set email alerts
|

Examining social media adoption and change to the stakeholder communication paradigm in not-for-profit sport organizations

Abstract: The purpose of this study was to examine social media adoption within not-for-profit sport organizations to illuminate the impetus for change, the type of change undertaken, and change resistance. Using a contextualist approach depicting the external and internal forces as well as the change process, semi-structured interviews were conducted with ten Canadian national sport organizations (NSO) representing varying degrees of social media presence. The findings suggest that, although social media is espoused as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Social media can serve as a vehicle to achieve strategic brand objectives (Sanderson & Yandle, 2015), if social media is well developed and properly managed (Naraine & Parent, 2017a, 2017b. This relationship between brand governance, stakeholders and social media has yet to be explored amongst NSOs.…”
Section: Brand Governance Practices In Canadian National Sport Organimentioning
confidence: 99%
See 3 more Smart Citations
“…Social media can serve as a vehicle to achieve strategic brand objectives (Sanderson & Yandle, 2015), if social media is well developed and properly managed (Naraine & Parent, 2017a, 2017b. This relationship between brand governance, stakeholders and social media has yet to be explored amongst NSOs.…”
Section: Brand Governance Practices In Canadian National Sport Organimentioning
confidence: 99%
“…While NSOs have experience in virtualizing themselves and developing relationships in an online space (see Girginov et al, 2009), the ferocity with which social media has pervaded the sport industry has simultaneously been a challenge and opportunity for NSOs. Notably, a slate of inquiry by Naraine and Parent (2016a, 2016b, 2017a, 2017b sought to understand NSOs and social media more intimately. One study in particular revealed these sport organizations embraced social media to demonstrate relevancy, keep stakeholders updated, and connect to new groups (Naraine & Parent, 2017a).…”
Section: Brand Governance Nsos and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical findings on the issues of digitalization in VSCs or sport federations often relate to the use of communication tools (Bingley and Burges, 2012). Results suggest that the benefits of communication tools are reduced by limited organizational capacities, employees' resistance (Naraine and Parent, 2017) and decision makers' lack of familiarity (Denison and Johanson, 2007). To provide a guide for evaluating mobile technology applications by VSCs, four mobile utility factors (ubiquity, convenience, interactivity and personalization) and three innovation adoption determinants (cost, skill requirements and compatibility) are proposed (Sellitto et al , 2016).…”
Section: Introductionmentioning
confidence: 99%